2016
DOI: 10.1186/s40200-016-0274-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between bone turnover markers and microvascular complications of type 2 diabetes

Abstract: BackgroundGlobal epidemic of diabetes is a serious health care concern because of its complications and consequently reduced life expectancy and increased morbidity. However, the bone turnover and thus bone health may be affected or even compromised by diabetes and its complications. The aim of this study was to assess whether bone turnover markers are associated with diabetes micro-vascular complications.MethodsA total of 204 type 2 diabetes patients (104 patients with diabetic micro-vascular complications (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
1
16
2
Order By: Relevance
“…[1] Moreover, only CTX and OC were proper bone markers in CAD patients with Type 2 DM, [19] however, no significant relation of OC to cardiovascular risk in our study. Study in Thai population was conducted to compare bone turnover between healthy people and CAD patients using biochemical markers of bone formation and resorption; and found that CAD patients have no higher risk for osteoporosis than healthy people.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…[1] Moreover, only CTX and OC were proper bone markers in CAD patients with Type 2 DM, [19] however, no significant relation of OC to cardiovascular risk in our study. Study in Thai population was conducted to compare bone turnover between healthy people and CAD patients using biochemical markers of bone formation and resorption; and found that CAD patients have no higher risk for osteoporosis than healthy people.…”
Section: Discussioncontrasting
confidence: 57%
“…[16] Elevating of Thai aging population is a trend to increase with the number of osteoporosis in elderly [17] and will be fast increase along with common chronic diseases, such as diabetes mellitus and cardiovascular diseases. [18,19] From Thai nation-wide survey (during 2000-2001), the age-adjusted prevalence of osteoporosis in Thai women ranging in age from 40 to 80 years was 13.6% and 19.8% for femoral neck and lumbar spine, respectively. For men, the age-adjusted prevalence of osteoporosis was 12.6, 4.6, and 3.9% at the femoral neck, lumbar spine, and both sites, respectively.…”
Section: Original Articlementioning
confidence: 99%
“…At baseline, there was a significant association between a higher degree of LINE‐1 methylation and lower diastolic blood pressure, lower cholesterol/HDL ratio and lower eGFR. A previous study in T2DM individuals described higher DNA methylation levels in patients with albuminuria compared with those without albuminuria . In that study there was a significant increasing trend in global DNA methylation levels in relation to albuminuria categories (normal range of albuminuria/microalbuminuria/macroalbuminuria).…”
Section: So What Does It Mean?mentioning
confidence: 61%
“…A previous study in T2DM individuals described higher DNA methylation levels in patients with albuminuria compared with those without albuminuria. 7 In that study there was a significant increasing trend in global DNA methylation levels in relation to albuminuria categories (normal range of albuminuria/microalbuminuria/macroalbuminuria). It is noteworthy that the overall methylation level was quite high across the four CpG sites studied in the T2DM patients studied here.…”
Section: So What Doe S It Me An?mentioning
confidence: 80%
“…[5] In Thailand, the increment of life period is a trend to increase the number of elders and the rate of osteoporosis will be rapidly increased [6] along with common chronic diseases, such as diabetic mellitus and cardiovascular diseases. [7][8][9]…”
Section: Introductionmentioning
confidence: 99%